Unionism as perceived by faculty and employees of selected private schools in Region IV : a study - Mendoza, Ricardo M. (Manila : National University, 2005)
This study was focused on probing labor-management relations in selected schools in Region IV. These are schools with identified union groups. The study was limited to the views of the union members and administrators in an academic setting.
Title Page -- Approval Sheet-- Abstract -- Table of Contents -- List of Tables -- Chapter 1: The Problem and its Background -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices .
Research Method: Descriptive Design.
Includes bibliographical references.